Thermoelectric material composite diaphragm, preparation method thereof and battery

By using thermoelectric material composite separators in alkali metal secondary batteries, using the combination of pyroelectric crystals and organic thermoelectric materials, the problem of slow lithium ions migration at low temperatures is solved, and the rate performance and cycle life of the battery are significantly improved, achieving More stable battery performance.

CN119297528APending Publication Date: 2025-01-10CHANGSHA GUNENG NEW ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411458224.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

At present, the alkali metal secondary batteries have slow ion migration speed and short cycle life at low temperatures, resulting in poor rate performance, especially the performance of lithium-ion batteries under low temperature conditions.

Method used

The thermoelectric material composite separator is used to coat the base film with pyroelectric transistors and organic thermoelectric materials to promote the removal and migration of lithium ions and improve the low-temperature magnification performance of the battery. The thermoelectric material coating contains pyroelectric transistors such as Li2SO4, ZnO, and CaS. The combination of organic thermoelectric materials and inorganic thermoelectric materials ensures uniformity of particle distribution and consistent performance.

Benefits of technology

It significantly improves the rate performance and cycle life of the battery at low temperatures, enhances the migration rate of lithium ions, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297528A_ABST
    Figure CN119297528A_ABST
Patent Text Reader

Abstract

The invention provides a thermoelectric material composite diaphragm, a preparation method thereof and a battery, the thermoelectric material composite diaphragm is composed of a base film and a thermoelectric material coating arranged on the surface of the base film, and the thermoelectric material coating comprises pyroelectric crystals; the pyroelectric crystal is selected from at least one of Li2SO4, ZnO, CaS and CaSe, and the preparation method comprises the following steps: dissolving an organic thermoelectric material in a certain proportion in an organic solvent, adding an inorganic thermoelectric material to form a suspension, then coating the surface of the diaphragm with the suspension, and then performing high-temperature drying to obtain the thermoelectric material composite diaphragm. The preparation method is simple and controllable, the prepared thermoelectric material coating can generate positive and negative charges at a low temperature to deviate from the center so as to induce a polarization phenomenon, and under the condition that a negative dipole faces outwards, separation of positive lithium ions is accelerated, so that the rate capability of the lithium battery at the low temperature is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of alkali metal secondary batteries, and in particular relates to a thermoelectric material composite diaphragm and a preparation method and a battery. Background Art

[0002] Alkali metal secondary batteries are now widely used in various fields of our lives, such as portable electronic devices, new energy vehicles, wind, solar and storage integration, etc., greatly improving people's quality of life.

[0003] However, there are still many problems with secondary batteries at this stage, such as insufficient cycle life, poor performance in a wide temperature range, especially poor rate performance at low temperatures, and the battery capacity is very different from that at normal temperature. Therefore, it is crucial to improve the overall rate performance of battery devices to meet applications in the entire territory and climate range. Among them, improving the ion migration rate is the core, including improving the conductivity of the positive electrode, the conductivity of the electrolyte, and the conductivity of the electrode, which enhances the rate performance of the battery to a certain extent. However, at low temperatures, the inherent properties of the positive electrode and the organic electrolyte cause the ion mobility to be greatly reduced. It is necessary to promote the escape of ions in the positive electrode and particularly enhance the migration rate of ions in the electrolyte, which will greatly promote the improvement of the rate performance of lithium batteries. Summary of the invention

[0004] In order to solve the problems of slow ion migration and short cycle life of batteries at low temperatures, the first object of the present invention is to provide a thermoelectric material composite diaphragm. The present invention promotes the escape of ions from the positive electrode and their migration in the electrolyte through the design of the composite diaphragm interface layer to improve its rate performance.

[0005] The second object of the present invention is to provide a method for preparing a thermoelectric material composite diaphragm. The preparation method provided by the present invention is simple to operate and has great practical application value.

[0006] The third object of the present invention is to provide a battery comprising the thermoelectric material composite membrane.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] The present invention provides a thermoelectric material composite diaphragm, which is composed of a base film and a thermoelectric material coating arranged on the surface of the base film, wherein the thermoelectric material coating contains pyroelectric crystals; the pyroelectric crystals are selected from at least one of Li2SO4, ZnO, CaS, and CaSe, and are preferably selected from at least one of Li2SO4 and CaS.

[0009] The thermoelectric material composite diaphragm provided by the present invention comprises pyroelectric crystals in the thermoelectric material coating. The pyroelectric crystals are polarized at low temperatures due to the deviation of the positive and negative charges of the crystals from the center, and the negative dipoles are distributed on the outer surface, thereby promoting the release of lithium ions and improving the low-temperature rate performance of the battery.

[0010] In a preferred embodiment, the thermoelectric material coating further comprises an organic thermoelectric material, and the organic thermoelectric material is selected from at least one of PVDF, P (VDF-HFP), and P (VDF-TrFE-CTFE). By combining the organic thermoelectric material with the inorganic thermoelectric material, the uniformity of particle distribution is ensured, and the performance consistency can also be improved.

[0011] In a preferred solution, the thickness of the thermoelectric material coating is 3 to 20 μm. In the present invention, the thickness of the thermoelectric material coating is controlled within the above range, and the final performance is optimal. If it is too thick, the ion migration path will be too long, which is not conducive to the improvement of rate performance. If it is too thin, the effect is not obvious.

[0012] In a preferred solution, the thickness of the base film is 9-20 μm. The base film has the best performance if it is within the above range. If it is too thin, the inorganic particles coating will easily pierce the diaphragm, and if it is too thick, the impedance will increase.

[0013] In a preferred embodiment, the base film is selected from one of polypropylene film, polyethylene film, polypropylene film / polyethylene film double-layer composite film, polypropylene film / polypropylene film double-layer composite film, polypropylene film / polyethylene film / polypropylene film three-layer composite film, and cellulose membrane, preferably polyethylene film, polypropylene film, and one of polypropylene film / polyethylene film double-layer composite film.

[0014] The present invention provides a method for preparing a thermoelectric material composite diaphragm, comprising adding an organic thermoelectric material into an organic solvent to obtain a solution A, adding an inorganic thermoelectric material into the solution A to obtain a suspension B, and coating the suspension B on the surface of a base film to obtain a thermoelectric material composite diaphragm;

[0015] The organic thermoelectric material is selected from at least one of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (P(VDF-HFP)), and poly(vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene) (P(VDF-TrFE-CTFE));

[0016] The inorganic thermoelectric material is selected from at least one of Li2SO4, ZnO, CaS, and CaSe, preferably at least one of Li2SO4 and CaS.

[0017] The preparation method of the present invention directly uses organic thermoelectric materials as binders, mixes with inorganic thermoelectric materials, and then coats them on the surface of a base film to obtain a thermoelectric material composite diaphragm. Not only can the inorganic materials be better adhered to the base film, but the organic thermoelectric materials are also used as thermoelectric materials. The combination of the organic thermoelectric materials and the inorganic thermoelectric materials ensures the uniformity of particle distribution and improves performance consistency, ultimately obtaining a thermoelectric material composite diaphragm with excellent performance.

[0018] In a preferred embodiment, the organic solvent is selected from at least one of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF) and tetrahydrofuran.

[0019] In a preferred embodiment, in the solution A, the mass ratio of the organic thermoelectric material to the organic solvent is 0.1:0.5 to 1. When the mass ratio of the organic thermoelectric material to the organic solvent is controlled within this range, the coating performance is optimal. If there is too much organic thermoelectric material, the slurry becomes viscous, which is difficult to coat and easily blocks the diaphragm pores; if there is too little organic thermoelectric material, the adhesion is weak and the inorganic thermoelectric material may fall off.

[0020] In a preferred embodiment, the organic thermoelectric material is added to an organic solvent and stirred at 45 to 60° C. to obtain solution A.

[0021] In a preferred embodiment, in the suspension B, the mass ratio of the organic thermoelectric material to the inorganic thermoelectric material is 0.05-0.2:0.8-0.95; preferably 0.05-1:0.9-0.95.

[0022] By controlling the mass ratio of organic thermoelectric materials to inorganic thermoelectric materials within the above range, it is possible to have a good adhesion effect without causing the organic thermoelectric materials to cover the crystals, thereby obtaining the best performance under the synergy of the organic thermoelectric materials and the inorganic thermoelectric materials. If too much organic thermoelectric material is added, it is easy to cover the crystals, and the inorganic material is not easy to exert its performance, and too little organic thermoelectric material will not be able to adhere.

[0023] In a preferred embodiment, the coating method is selected from spin coating, scraper coating, dip coating and spray coating.

[0024] In a preferred embodiment, after the suspension B is coated on the surface of the base film, it is dried at 60 to 80° C. for 6 to 20 hours to obtain a thermoelectric material composite diaphragm.

[0025] The present invention also provides a battery, wherein the battery comprises the thermoelectric material composite diaphragm.

[0026] Preferably, in the battery, the base film side of the thermoelectric composite diaphragm is close to the negative electrode, and the thermoelectric material coating side is close to the positive electrode. Through the above arrangement, the lithium ion transmission efficiency and interface stability on the positive electrode side can be regulated. When the battery is used at low temperature, the positive and negative charge centers of the thermoelectric material crystals are offset, inducing negative charges to move outward, thereby promoting the release of lithium ions and improving the low temperature rate performance of the battery.

[0027] Beneficial Effects

[0028] The thermoelectric material composite diaphragm provided by the present invention comprises pyroelectric crystals in the thermoelectric material coating. The pyroelectric crystals are polarized at low temperatures due to the deviation of the positive and negative charges of the crystals from the center, and the negative dipoles are distributed on the outer surface, thereby promoting the release of lithium ions and improving the low-temperature rate performance of the battery.

[0029] The preparation method of the present invention directly uses organic thermoelectric materials as binders, mixes with inorganic thermoelectric materials, and then coats them on the surface of a base film to obtain a thermoelectric material composite diaphragm. Not only can the inorganic materials be better adhered to the base film, but the organic thermoelectric materials are also used as thermoelectric materials. The combination of the organic thermoelectric materials and the inorganic thermoelectric materials ensures the uniformity of particle distribution and improves performance consistency, ultimately obtaining a thermoelectric material composite diaphragm with excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Performance comparison chart of Example 1 and Comparative Example 1 at low temperature -40°C. DETAILED DESCRIPTION

[0031] Embodiment 1:

[0032] The mass ratio of the organic thermoelectric material PVDF to the organic matter NMP is controlled to be 0.1:1, and mixed to form a solution; then the inorganic thermoelectric material Li2SO4 is added, and the mass ratio of PVDF to Li2SO4 is controlled to be 0.1:0.9, and PVDF+Li2SO4=1. After obtaining a mixed slurry, the mixed slurry is applied on the surface of a polyethylene diaphragm by a doctor blade method, and then dried at 65°C for 10 hours to obtain a thermoelectric material composite diaphragm, wherein the thickness of the thermoelectric material composite diaphragm is 25 μm, wherein the thickness of the polyethylene diaphragm is 20 μm, and the thickness of the thermoelectric material coating is 5 μm;

[0033] High nickel ternary NCM811 is used as the positive electrode, and the mass ratio of NCM811: carbon black: PVDF is 8:1:1. They are mixed evenly to form a slurry, which is evenly coated on an aluminum foil and cut into positive electrode sheets with a diameter of 12 mm. Lithium metal is used as the negative electrode, and a thermoelectric material composite diaphragm is used as the diaphragm. A CR2016 button battery is assembled in a glove box, which is the battery of Example 1.

[0034] For comparison, the battery of Comparative Example 1 uses a common polyethylene separator and is assembled into a CR2016 button battery under the same conditions. The above battery is subjected to charge and discharge cycle tests under the same test equipment and test conditions, wherein the voltage range of the full battery test is 3 to 4.3V and the test temperature is -40°C. Figure 1 The battery capacity of Example 1 is 105.8 mAh g at a current density of 1 C. -1 After 150 cycles, the capacity is still 98 mAh g -1 , while the capacity of comparative example 1 at 1C is only 46.2 mAh g -1 After 150 cycles, the capacity is 31.9 mAh g -1 .

[0035] Embodiment 2:

[0036] Compared with Example 1, the only difference is that the thermoelectric material coating is CaS, and its mass ratio and thickness remain unchanged. Its capacity is 103.6 mAh g at a current density of 1C. -1 After 150 cycles, the capacity is still 97.3 mAh g -1 .

[0037] Embodiment 3:

[0038] Compared with Example 1, the only difference is that the diaphragm base film is a polypropylene film, and its mass ratio and thickness remain unchanged. Its capacity is 98.5 mAh g at a current density of 1C. -1 After 150 cycles, the capacity is still 93.5 mAh g -1 .

[0039] Embodiment 4:

[0040] Compared with Example 1, the only difference is that the ratio of organic thermoelectric material PVDF to inorganic thermoelectric material Li2SO4 is 0.15:0.85, and the thickness remains unchanged. Its capacity at a current density of 1C is 94.3 mAh g -1 After 140 cycles, the capacity is still 90.1 mAh g -1 .

[0041] Comparative Example 1

[0042] The battery uses ordinary polyethylene separator.

[0043] Comparative Example 2:

[0044] Compared with Example 1, the only difference is that it uses a polyethylene separator with a thickness of 25 μm, and its capacity at 1C is only 46.2 mAh g -1 After 150 cycles, the capacity is 31.9 mAh g -1 .

[0045] Comparative Example 3:

[0046] Compared with Example 1, the only difference is that the binder uses styrene-butadiene rubber SBR, and the capacity is only 54.2 mAhg at 1C. -1 After 150 cycles, the capacity is 48.9 mAh g -1 .

[0047] Comparative Example 4:

[0048] Compared with Example 1, the only difference is that the thickness of the coating layer is increased while the thickness of the base film remains unchanged. The total thickness of the composite diaphragm is 50 μm, and the capacity is only 38.7 mAh g at 1C. -1 After 150 cycles, the capacity is 35.4 mAh g -1 .

[0049] Comparative Example 5:

[0050] Compared with Example 1, the only difference is that the thickness of the coating is reduced while the thickness of the base film remains unchanged. The total thickness of the composite diaphragm is 21 μm, and the capacity is only 49.8 mAh g at 1C. -1 After 150 cycles, the capacity is 47.2Ah g -1 .

[0051] Comparative Example 6:

[0052] Compared with Example 1, the only difference is that the inorganic thermoelectric material is Ag2S, and the capacity is only 40.1 mAh g at 1C. -1 After 150 cycles, the capacity is 35.5 mAh g -1 .

Claims

1. A thermoelectric material composite diaphragm, characterized in that: The thermoelectric material composite diaphragm is composed of a base film and a thermoelectric material coating arranged on the surface of the base film, and the thermoelectric material coating contains pyroelectric crystals; the pyroelectric crystals are selected from at least one of Li2SO4, ZnO, CaS, and CaSe.

2. A thermoelectric material composite diaphragm according to claim 1, characterized in that: The thermoelectric material coating further comprises an organic thermoelectric material, and the organic thermoelectric material is selected from at least one of PVDF, P (VDF-HFP), and P (VDF-TrFE-CTFE).

3. A thermoelectric material composite diaphragm according to claim 1 or 2, characterized in that: The thickness of the thermoelectric material coating is 3-20 μm.

4. A thermoelectric material composite diaphragm according to claim 1 or 2, characterized in that: The thickness of the base film is 9 to 20 μm; The base film is selected from one of polypropylene film, polyethylene film, polypropylene film / polyethylene film double-layer composite film, polypropylene film / polypropylene film double-layer composite film, polypropylene film / polyethylene film / polypropylene film three-layer composite film, and cellulose separator.

5. The method for preparing a thermoelectric material composite diaphragm according to any one of claims 1 to 4, characterized in that: Adding an organic thermoelectric material into an organic solvent to obtain a solution A, adding an inorganic thermoelectric material into the solution A to obtain a suspension B, and coating the suspension B on the surface of the base film to obtain a thermoelectric material composite diaphragm; The organic thermoelectric material is selected from at least one of PVDF, (P(VDF-HFP)), and (P(VDF-TrFE-CTFE)); The inorganic thermoelectric material is selected from at least one of Li2SO4, ZnO, CaS and CaSe.

6. The method for preparing a thermoelectric material composite diaphragm according to claim 5, characterized in that: The organic solvent is selected from at least one of NMP, DMF and tetrahydrofuran; In the solution A, the mass ratio of the organic thermoelectric material to the organic solvent is 0.1:0.5-1; The organic thermoelectric material is added into an organic solvent and stirred at 45-60° C. to obtain a solution A.

7. The method for preparing a thermoelectric material composite diaphragm according to claim 5, characterized in that: In the suspension B, the mass ratio of the organic thermoelectric material to the inorganic thermoelectric material is 0.05-0.2:0.8-0.

95.

8. The method for preparing a thermoelectric material composite diaphragm according to claim 5 or 7, characterized in that: The coating method is selected from spin coating, scraper coating, dip coating, and spray coating; After the suspension B is coated on the surface of the base film, it is dried at 60-80° C. for 6-20 hours to obtain a thermoelectric material composite diaphragm.

9. A battery, characterized in that: The battery comprises the thermoelectric material composite diaphragm according to any one of claims 1 to 4.

10. A battery according to claim 9, characterized in that: In the battery, the base film side of the thermoelectric composite diaphragm is close to the negative electrode, and the thermoelectric material coating side is close to the positive electrode.